Pengaruh Pemberian Rebusan Daun Pepaya Terhadap Produksi Asi Pada Ibu Nifas Di Wilayah Kerja Puskesmas Tinondo Kab. Kolaka Timur - Yenni Yenni; Andi Tenri Angka (Jurnal Rumpun Ilmu Kesehatan, 2022)
Breast milk production can be increased, one way is by consuming vegetables. The types of vegetables that can increase breast milk production include katuk leaves, young papaya leaves, moringa leaves and lembayung leaves. Consumption of young papaya leaves is still rarely done by breastfeeding mothers. Young papaya leaves are a natural plant that acts as a lactogogum because it can increase and facilitate breast milk. Research objective: The effect of giving boiled papaya leaves on breast milk production in postpartum mothers in the working area of the Tinondo District Health Center. East Kolaka in 2021. The type of research used was a quasi-experimental method. The sample in the research was all postpartum mothers who were not breastfeeding smoothly at the Tinondo District Health Center. East Kolaka, namely 21 people using a purposive sampling technique. There is an effect of giving boiled papaya leaves on breast milk production in postpartum mothers in the working area of ​​the Tinondo District Health Center. East Kolaka in 2021 where the results of measuring breast milk production before being given treatment obtained an average value of 3271.43 to an average value of measuring breast milk production of 3590.48 after being given boiled papaya leaves with a sig value (2-tailed) 0.000 < 0.05. Suggestions for health workers should be used as information about the smoothness and production of breast milk for postpartum mothers.